Minimally disruptive optical control of protein tyrosine phosphatase 1B - Akarawin Hongdusit (Nature Portfolio, 2020)
Protein tyrosine phosphatases regulate many cellular processes but are difficult to study in their native context. Here the authors develop an approach for using light to control the activity of a disease-relevant phosphatase without interfering with its native cellular organization.